MATTAMPUNG MASSAL DI DESA HARAPAN KECAMATAN TANETE RIAJA KABUAPATEN BARRU - Rahmi, Nur (FAJAR HISTORIA: Jurnal Ilmu Sejarah dan Pendidikan, 2018)
The results of this study indicate that: (1) The functions of the implementation of mattampung in Harapan Village besides continuing the habits of previous parents, mattampung also functions as a marker for subsequent generations in recognizing siblings or families who have already died. (2) mattampung massa is held once a year in October. After the decision of the adat council is obtained through a process of deliberation. Mass gathering is carried out by preparing betel nut and betel nut leaves, three chickens will be read to the next prayer in give to the customary leader and be taken to the tomb of the deceased person as food for the deceased because the community believes that when the deceased person has not been accommodated, they can still eat like a living person. (3) The values contained in the implementation of mattampung in social terms are the value of mutual cooperation, the value of wisdom or togetherness and the value of friendship. While in terms of the economy, the community is greatly helped by the existence of mass mattampung.